Semiotika Poster Instagram Muslim Designer Community: Perspektif Dakwah - Muhammad vikri Ardiansyah; Sunaryanto (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2024)
This study uses a qualitative approach with a constructivist paradigm to analyze the social meanings in the symbols of the Instagram posters from @MuslimDesignerCommunity. The focus is on how meanings are produced and interpreted within the cultural and communication context of da'wah. Data was collected through documentation and digital observation, with a semiotic analysis using Ferdinand de Saussure's theory on six of the most popular posters published on the @MuslimDesignerCommunity account in June-July 2024. The research concludes that the da'wah message in the posters published by the @muslimdesigner account during June-July 2014 covers three key aspects: akhlak (morality), aqidah (faith), and ibadah (worship). The moral message emphasizes the importance of guarding the heart, reflecting on the Qur'an, collaborating to solve problems, and making the best use of time. In terms of faith, the message encourages submission to Allah SWT, repentance from sinful acts, and relying solely on Him. Meanwhile, the worship message calls on the community to fast on the days of Arafah and Ashura, as well as to pray to Allah SWT. Semiotic analysis shows that the posters convey Islamic values in line with the teachings of the Qur'an and Hadith, as reflected in Surah Al-Ahzab (33:21) which states that the Prophet Muhammad SAW is a "good example" (uswatun hasanah), and the Hadith encouraging fasting on Arafah and Ashura as acts of worship that bring one closer to Allah SWT.